Sistem Informasi Pelayanan Gereja Berbasis Web di Gereja Bethel Indonesia Juwana - Christian Yoga Megatama; Aditya Akbar Riadi; Evanita Evanita (Sekawan Institut, 2025)
This research aims to develop a web-based information system at the Bethel Indonesia Church (GBI) Juwana to improve the efficiency of delivering information to the congregation, especially for congregants who cannot attend services. In this rapidly developing era, information technology has become an important part of daily life, including in communication between churches and their congregations. Currently, information about church activities is mostly conveyed through direct announcements, so that some congregations miss important information. To overcome this, a web-based information system was created that makes it easy for congregants to access church-related information, such as service schedules, announcements, activity registration, devotionals, and photo galleries. Method. The development method used for this system is the Waterfall Model, which includes stages such as requirements analysis, design, implementation, testing, and maintenance. The completed system is expected to answer the challenges of church communication, reduce information errors, and increase congregational access. The test results show that all features function properly, both for information management by the admin and for information access by the congregation. With this system, the church is expected to be more effective in disseminating information and increasing congregational engagement, even for those who cannot attend church activities in person.